(untitled) - Packard, Truman G. (Washington, D.C., 2014)
This report argues that the appropriate policy responses are to ensure macroeconomic stability, and in particular, a regulatory framework that encourages small- and medium-sized enterprises where most people in the region work. Mainly agrarian countries should focus on raising agricultural productivity. In urbanizing countries, good urban planning becomes critical. Pacific island countries will need to provide youth with human capital needed to succeed abroad as migrant workers. And, across the region, it is critical to ‘formalize’ more work, to increase the coverage of essential social protection, and to sustain productivity. To this end, policies should encourage mobility of labor and human capital, and not favor some forms of employment - for instance, full-time wage employment in manufacturing - over others, either implicitly or explicitly. Policies to increase growth and well-being from employment should instead reflect and support the dynamism and diversity of work forms across the region.
Keywords: Labor,Labor,East Asia,Pacific Area,Lao động,Lao động,Đông Á,Khu vực Thái Bình Dương; Economic conditions,Economic conditions,Điều kiện kinh tế,Điều kiện kinh tế; 21st century,21st century,Thế kỷ 21,Thế kỷ 21; East Asia,Pacific Area,Đông Á,Thái Bình Dương